Optical transition properties, internal quantum efficiencies, and temperature sensing of Er3+ doped BaGd2O4 phosphor with low maximum phonon energy. Issue 5 (3rd January 2022) - Luo, Mengyan; Sha, Xuezhu; Chen, Baojiu; Zhang, Xizhen; Yu, Hongquan; Li, Xiangping; Zhang, Jinsu; Xu, Sai; Cao, Yongze; Wang, Yichao; Wang, Xin; Zhang, Yuhang; et al.
Abstract: The hosts with low maximum phonon energy (MPE) are preferred since the nonradiative consumption of the luminescence centers in them are low. Among the low MPE hosts, the oxide ones are more favored owing to their excellent stability and easy synthesis. In this work, the optical and spectroscopic properties of BaGd2 O4 :Er 3+ phosphor were studied. The MPE of BaGd2 O4 host was observed from Eu 3+ phonon sideband (PSB) spectrum and Raman spectrum to be 477 cm −1 which does not second to the fluoride hosts. The refractive index, which is indispensable for Judd–Ofelt calculation, was confirmed from the both approaches of the Eu 3+ ‐probe and the band gap energy, and the similar refractive indices were confirmed, therefore the average refractive index 2.01 was used in the Judd–Ofelt calculation. The Judd–Ofelt parameters of Er 3+ in BaGd2 O4 host was confirmed to be Ω 2 ${Ω _2}\;$ = 7.91 × 10 −21 cm 2, Ω 4 ${Ω _4}\;$ = 2.36 × 10 −21 cm 2, and Ω 6 ${Ω _6}\;$ = 9.00 × 10 −22 cm 2 . Furthermore, the internal quantum efficiencies for 4 F9/2 and 4 I J ( J = 9/2, 11/2, and 13/2) levels were determined. Finally, the optical temperature sensing properties were studied in detail, and the temperature calibration curve was experimentally derived, meanwhile the maximum absolute sensitivity was confirmed to be 0.0028 K −1 .